2006
DOI: 10.1128/mmbr.00020-06
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Perception in Bacterial Signal-Transducing Histidine Kinases

Abstract: SUMMARY Two-component signal-transducing systems are ubiquitously distributed communication interfaces in bacteria. They consist of a histidine kinase that senses a specific environmental stimulus and a cognate response regulator that mediates the cellular response, mostly through differential expression of target genes. Histidine kinases are typically transmembrane proteins harboring at least two domains: an input (or sensor) domain and a cytoplasmic transmitter (or kinase) domain. They can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
666
0
16

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 624 publications
(687 citation statements)
references
References 288 publications
(312 reference statements)
5
666
0
16
Order By: Relevance
“…There are also hybrid RRs (HRRs) containing HK domains [27,28]. There are 35 different families of RRs based on different types of output domains [22,26,29]. Approximately 50% of the activated RRs undergo homodimerization involving conserved residues at their receiver domains, and dimer formation is required for interaction with the regulatory regions of the target genes, which may contain tandem and inverted repeats [16,22].…”
Section: How Tcss Workmentioning
confidence: 99%
See 2 more Smart Citations
“…There are also hybrid RRs (HRRs) containing HK domains [27,28]. There are 35 different families of RRs based on different types of output domains [22,26,29]. Approximately 50% of the activated RRs undergo homodimerization involving conserved residues at their receiver domains, and dimer formation is required for interaction with the regulatory regions of the target genes, which may contain tandem and inverted repeats [16,22].…”
Section: How Tcss Workmentioning
confidence: 99%
“…Although sequence analyses of bacterial genomes reveals a diverse array of TCSs based on their conserved domain architecture, there is still limited information about their biological functions, and few studies have identified the stimuli responsible for HK activation [29]. Experimental studies and comparative genome analysis indicate that arrangement and topology of the N-terminal sensor and TM domains of HKs correlate with the type of stimuli sensed [30].…”
Section: How Tcss Workmentioning
confidence: 99%
See 1 more Smart Citation
“…TCS는 원래 박테리아의 외부환경 감지 센 서로서 다양한 환경 변화를 감지하는 기능을 한다 (Stock et al, 2000). 각각의 TCS는 외부의 환경 변화를 감지하는 histidine kinase (HK)와 외부신호를 전달받아 관련 유전자의 발현을 유도 하는 response regulator (RR)로 구성되어 있다 (Mascher et al, 2006). 현재까지 밝혀진 TCS 중에서 ZraS/R은 외부의 Zn 2+ 를 감지하여 아연 efflux 연관 유전자인 zraP의 발현을 유도하여 균 주 내부의 아연 농도를 낮추고 항상성을 유지하는 역할을 수행…”
Section: Two-component System (Tcs)-based Bacterial Zinc and Copper Bunclassified
“…TCS는 원래 박테리아의 외부환경 감지 센 서로서 다양한 환경 변화를 감지하는 기능을 한다 (Stock et al, 2000). 각각의 TCS는 외부의 환경 변화를 감지하는 histidine kinase (HK)와 외부신호를 전달받아 관련 유전자의 발현을 유도 하는 response regulator (RR)로 구성되어 있다 (Mascher et al, 2006 한다. 또한 CusS/R TCS는 Cu 2+ 를 감지하여 구리 efflux와 연관된 cusC 유전자를 발현시킨다 (Munson et al, 2000;Leonhartsberger et al, 2001).…”
unclassified